An investigation of cerebral bridging veins rupture due to head trauma. Issue 7 (19th May 2023) - Abdi, Hamed; Hassani, Kamran; Shojaei, Shahrokh
Abstract: Subdural hematoma (SDH) is common abnormality that is caused by the rupture of cerebral bridge veins (BVs). It occurs in more than 30% of severe head injuries. The purpose of this research was to develop a numerical model to examine the effects of brain atrophy and age on the rupture of bridging veins in subdural hematoma. Three types of models were developed to simulate subdural hematoma, namely global solid, global FSI, and local solid models. In the next step, a head impact with the head injury criterion (HIC) value of 744 was applied as a loading condition to global models. For the global solid models, we measured the relative displacement between the skull and brain. We extracted the pressure distribution from the global FSI models. The data were used as boundary conditions on the local models to evaluate the damage to the cerebral bridge veins precisely The results showed that the relative displacement was greater in the atrophied model compared to the healthy one (2.64 and 2.20 mm, respectively). In addition, the pressure value was higher in atrophied models. In the healthy local model, the maximum strain on BVs was around 1.38, while in the atrophied model, it was 2.77. The head impact, which had a HIC value of 744, did not cause serious injury to a human with a healthy brain, but it caused severe damage to an atrophied brain. The degeneration of the brain and intracranial space changes are two important factors for the movement of the brain and its vulnerability to impact.